(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Educational and sports work with teenagers should be considered as leading to active sports activities. Groups should be based on age, physical development and, preferably, weight category. This is convenient, because it will be possible to choose exercises for all those involved in the group.